(untitled) (Journal of Pharma Insights and Research, 2024)
Pharmacovigilance plays a crucial role in monitoring the safety of herbal, homeopathic, and allopathic drugs, particularly for treatments of hypertension and kidney diseases. The global increase in complementary and alternative medicine use alongside conventional therapies necessitates a thorough understanding of potential interactions and side effects. Current pharmacovigilance systems for herbal and homeopathic remedies face unique challenges compared to established allopathic drug monitoring processes. Recent research on allergic reactions to these diverse therapeutic approaches reveals varying prevalence, mechanisms, and clinical implications. Regulatory frameworks governing these treatment modalities differ across countries, highlighting the need for harmonized international standards. Emerging technologies, including artificial intelligence and big data analytics, show promise in enhancing adverse drug reaction (ADR) detection and prevention. Integration of findings from multiple disciplines provides healthcare professionals, researchers, and policymakers with insights into ensuring safe use of herbal, homeopathic, and allopathic drugs in managing hypertension and kidney diseases. This review summarizes current knowledge, identifies research gaps, and proposes future directions for improving pharmacovigilance across these diverse therapeutic approaches